2010
DOI: 10.1603/ec10169
|View full text |Cite
|
Sign up to set email alerts
|

Development of Allele-Specific Single-Nucleotide Polymorphism-Based Polymerase Chain Reaction Markers in Cytochrome Oxidase I for the Differentiation of Bactrocera papayae and Bactrocera carambolae (Diptera: Tephritidae)

Abstract: Differentiation of Bactrocera papayae Drew & Hancock and Bactrocera carambolae Drew & Hancock (Diptera: Tephritidae) based on morphological characters has often been problematical. We describe here a single-nucleotide polymorphism (SNP)-based polymerase chain reaction (PCR) assay to differentiate between these two species. For detection of SNPs, fragments derived from each species were amplified using two primer pairs, COIF/COIR and UEA7/UEA10, sequenced, and aligned to obtain a contiguous 1,517-bp segment. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Due to the unresolved clade of B. dorsalis and B. papayae, Boykin et al (2013) concluded that they are the same biological species. A recent study by Chua et al (2010) also successfully differentiates B. carambolae and B. papayae using SNP-PCR analyses. Therefore, these findings disprove the concluding remarks by Drew (1994), which were based on external morphology and declared that the species resembled each other and were no different.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Due to the unresolved clade of B. dorsalis and B. papayae, Boykin et al (2013) concluded that they are the same biological species. A recent study by Chua et al (2010) also successfully differentiates B. carambolae and B. papayae using SNP-PCR analyses. Therefore, these findings disprove the concluding remarks by Drew (1994), which were based on external morphology and declared that the species resembled each other and were no different.…”
Section: Discussionmentioning
confidence: 94%
“…Several Bactrocera species are also known as problematic economic pests that infest and damage a wide variety of crops in Malaysia. The infestation of Bactrocera species consequently reduces production yields and the quality of the crops (Chua et al 2010). Therefore, accurate identification of Bactrocera species is highly important for the successful management of targeted pest and quarantine initiatives (Asokan et al 2011;Liu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chua et al . [66] describe an allele-specific diagnostic PCR-assay for Bactrocera carambolae and B . papayae based on COI.…”
Section: Discussionmentioning
confidence: 99%
“…However, this method is time-consuming and costly because of the sequencing process. Some recent studies have used PCR with species-specific primer pairs to make the identification more rapid based only on the presence or absence of a band in the gel profile, thereby overcoming the need for post-amplification digestion and sequencing (Hosseini et al 2007;Chua et al 2010;Zhang et al 2012).…”
Section: Introductionmentioning
confidence: 99%